Beeinflussung des Risswachstums durch Kerben in additiv gefertigten Strukturen - Reschetnik, W.; Brüggemann, J.P.; Kullmer, G.; Risse, L. (Additive Fertigung von Bauteilen und Strukturen – Neue Erkenntnisse und Praxisbeispiele)

Optimierung der Werkstoffperformance lasergeschmolzener metallischer Werkstoffe - Riemer, A.; Leuders, S.; Richard, H.A.; Kullmer, G.

Konstruktionsregeln für additive Fertigung in Lehre und Forschung - Adam, Guido; Zimmer, Detmar (Newsletter Berliner Kreis)

FDM Part Quality Manufactured with ULTEM 9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (Proceedings of International Conference Polymeric Materials)
Generative production techniques have the advantage of manufacturing parts via an additive process without needing a forming tool. One of these additive manufacturing technologies is “Fused Deposition Modeling” (FDM). From a 3D-CAD data set, components and assemblies are manufactured out of thermoplastic material in only a few working steps. Native software automatically slices the data, calculates the support structures, and creates toolpaths. The parts then are built up layer by layer by means of an additive process. An extrusion head deposits the molten thermoplastic filament to create each layer. This technology began as a process for creating prototype parts; recently it has found new utility in the production of manufacturing tools and as a manufacturing process for end-use parts. In order to be used as a part for serial production, the components must possess the required mechanical properties. To this end, not only is the chosen material relevant, but a correct process control is also necessary. An interesting material for the aircraft and automotive industry is the material PEI with the trade name Ultem*9085. This material should typically be used on FDM-machines for the manufacturing of end products. The aim of the research is to determine the present mechanical data based on the process control, as well as reproducibility from job to job. In this work the influence of the orientation and the structure of the manufactured parts based on the mechanical data are analyzed. Sample parts are generated with the given parameters of the native software based upon the CAD data. First, specimens were analyzed concerning their geometry and configuration. The dimensions and weight were measured. The mechanical tests conducted were the tensile and compression tests.

Mechanical and Physical Properties - A Way to asses quality of Laser Sintered Parts - Rüsenberg, Stefan; Schmidt, L.; Schmid, Hans-Joachim (22th Annual International Solid Freeform Fabrication Symposium)
The aim of this paper is the description and evaluation of physical properties like porosity and density and their influence on mechanical properties of laser sintered polyamide parts. For example, by reducing the porosity an increase of mechanical properties is possible. The correlation of laser parameters to these properties is investigated in detail. The energy density is an important parameter for the laser sintering process. By changing laser power, scan velocity and hatch distance an influence on manufactured components is given. A systematic variation of all three laser parameters is performed. A comparison of results obtained at constant energy densities obtained by varying these relevant parameters accordingly is shown as well.

Porosity as a key to increase material properties of laser sintered parts - Rüsenberg, Stefan; Schmidt, L.; Hosse, H.; Schmid, Hans-Joachim

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Mechanical Properties of Fused Deposition Modeling Parts Manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker (ANTEC)
In this work the influence of the orientation and the toolpath generation of manufactured parts based on the mechanical data are analyzed. Tensile Specimen are generated with the given parameters as well as with changing parameters of the native software based upon the CAD data. The parts then are built up with the “Fortus 400mc” from Stratasys. First tensile tests show different strength and strain characteristics that depend on the given structure and as a result of the build direction. The influence of the parameters was analyzed with a statistic test method by using the software Design Expert.

Controlling the Quality of Laser Sintered Parts Along the Process Chain - Rüsenberg, Stefan; Weiffen, R.; Knoop, F.; Schmid, Hans-Joachim (23rd Annual International Solid Freeform Fabrication Symposium)
The quality of laser sintered parts, in this work, manufactured by polymer laser sintering by using an EOSINT P395 Laser Sintering system, depends on several steps along the process chain. The first step is the characterization of the powder quality, whereas the rheological and physical investigations of nylon 12 powder are shown. By changing some important influencing factors, for example the powder ratio, the powder ageing and the moisture content, the influence on mechanical and physical properties, density and porosity, are investigated. The composition of the used powder is known. The previous process (storage conditions, etc.) as well as the laser sintering process (regarding energy density, temperature, etc.) is kept constant for the duration of this work. Regarding the post process in this work the cooling down phase is investigated as well. With an automatically blasting system it is possible to keep the post process parameters blasting distance and blasting time, constant. All of the tests will be performed using dry and conditioned test specimens. This work is showing the dependence on mechanical, rheological and physical parameters by varying important influencing factors along the laser sintering process quality chain.